Production and characterization of single-chain variable fragment antibodies targeting the breast cancer tumor marker nectin-4 - Liu, Ching-Hsuan; Leu, Sy-Jye; Lee, Chi-Hsin; Lin, Cheng-Yuan; Wang, Wei-Chu; Tsai, Bor-Yu; Lee, Yu-Ching; Chen, Chi-Long; Yang, Yi-Yuan; Lin, Liang-Tzung (Frontiers in Immunology, 2024)
Nectin-4 is a novel biomarker overexpressed in various types of cancers, including breast cancers, in which it has been associated with poor prognosis. Current literature suggests that nectin-4 has a role in cancer progression and may have prognostic and therapeutic implications. The present study aims to produce nectin-4-specific single-chain variable fragment (scFv) antibodies and evaluate their applications in breast cancer cell lines and clinical specimens. We generated recombinant nectin-4 ectodomain fragments as immunogens to immunize chickens and constructed anti-nectin-4 scFv libraries using phage display. The binding capacities of the selected clones were evaluated with the recombinant nectin-4 fragments, breast cancer cell lines, and paraffin-embedded tissue sections using various laboratory approaches. The binding affinity and in silico docking profile were also characterized. We have selected two clones (S21 and L4) from the libraries with superior binding capacity. S21 yielded higher signals when used as the primary antibody for western blot analysis and flow cytometry, whereas clone L4 generated cleaner and stronger signals in immunofluorescence and immunohistochemistry staining. In addition, both scFvs could diminish attachment-free cell aggregation of nectin-4-positive breast cancer cells. As results from ELISA indicated that L4 bound more efficiently to fixed nectin-4 ectodomain, molecular docking analysis was further performed and demonstrated that L4 possesses multiple polar contacts with nectin-4 and diversity in interacting residues. Overall, the nectin-4-specific scFvs could recognize nectin-4 expressed by breast cancer cells in vitro and ex vivo and have the merit of being further explored for potential diagnostic and therapeutic applications.